2009
DOI: 10.1002/nml.240
|View full text |Cite
|
Sign up to set email alerts
|

Transformational and transactional leadership styles, followers' positive and negative emotions, and performance in German nonprofit orchestras

Abstract: Although the transformational-transactional leadership paradigm has received increased attention from the research com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 48 publications
(51 reference statements)
2
71
0
3
Order By: Relevance
“…Finally, intellectual stimulation is related to encouragement of followers to reexamine assumptions about their work and to find creative ways of improving their performance. Many researchers (Liaw et al, 2010;MacKenzie et al, 2001;Rowold and Rohmann, 2009;Sarros and Santora, 2001;Tatum et al, 2003) view both transactional leadership and transformational leadership as effective at influencing followers' behaviors and include these two styles in their studies to examine the characteristics and the associated outcomes measured in such terms as customer orientation, job performance, trust, and role ambiguity. Because these two leadership styles are considered most effective at influencing others, the current study focuses on these two styles of leadership.…”
Section: Leadership Stylementioning
confidence: 99%
“…Finally, intellectual stimulation is related to encouragement of followers to reexamine assumptions about their work and to find creative ways of improving their performance. Many researchers (Liaw et al, 2010;MacKenzie et al, 2001;Rowold and Rohmann, 2009;Sarros and Santora, 2001;Tatum et al, 2003) view both transactional leadership and transformational leadership as effective at influencing followers' behaviors and include these two styles in their studies to examine the characteristics and the associated outcomes measured in such terms as customer orientation, job performance, trust, and role ambiguity. Because these two leadership styles are considered most effective at influencing others, the current study focuses on these two styles of leadership.…”
Section: Leadership Stylementioning
confidence: 99%
“…Note that, although researchers have previously studied some of the links in our research model in different contexts, such as the relationships between ESM and performance (Kuegler et al, 2015), positive emotions and performance (where there are inconclusive and mixed findings) (Rowold & Rohmann, 2009;Staw, Sutton, & Pelled, 1994), and workplace integration and performance (Orhan, Rijsman, & van Dikj, 2016), we are the first to study ESM as an antecedent of workplace integration and performance based on an integrated theoretical model of social capital theory and positive emotions theory.…”
mentioning
confidence: 99%
“…This shows the same result with [51] that leaders who provide employees training, knowledge and chance to challenge themselves, show confidence in the employee's ability and make employees feel their importance in the organization will help employee experience more positive mood. [52] stated that transformational leadership has strong connection with employee's positive emotion while transactional leadership is connected with negative emotion.…”
Section: H Positive Moodmentioning
confidence: 99%
“…On the contrary, negative emotion may decrease working motivation and high-level performance [57]. In [52], it was founded that negative emotion had a significant impact on performance. [46] reported that positive mood led to better creative outcome but it also make employee over-self-satisfaction that lead to reducing creativity.…”
Section: H Positive Moodmentioning
confidence: 99%